Complex Liver Resection Using Standard Total Vascular Exclusion, Venovenous Bypass, and In Situ Hypothermic Portal Perfusion: An Audit of 77 Consecutive Cases. Issue 1 (July 2015) - Azoulay, Daniel; Lim, Chetana; Salloum, Chady; Andreani, Paola; Maggi, Umberto; Bartelmaos, Tonine; Castaing, Denis; Pascal, Gérard; Fesuy, Feetal
Abstract : Objective: To identify independent predictors of 90-day mortality after liver resection for patients undergoing standard total vascular exclusion (TVE) with hypothermic portal perfusion and venovenous bypass. The secondary endpoint was to evaluate the long-term outcomes. Background: Tumors invading the vena cava and/or the hepatocaval confluence are indications for standard TVE. The inclusion of liver hypothermic perfusion permits safe TVE. There are a limited number of reports focusing on this complex technique and no relevant analysis of short-term and long-term results. Methods: Seventy-seven consecutive liver resections performed using standard TVE with hypothermic portal perfusion and venovenous bypass between 1998 and 2010 were analyzed. The independent predictors and rates of 90-day mortality, morbidity, and long-term survival were evaluated. Results: The 90-day mortality rate was 19.5% (15 cases). Three independent predictors of mortality were identified: age-adjusted Charlson Comorbidity Index 3 or more ( P = 0.0231; odds ratio = 47.565; 95% confidence interval = 1.701–1330.414), tumor size 10 cm or more ( P = 0.0442; odds ratio = 6.374; 95% confidence interval = 1.049–38.734), and the presence of 50/50 criteria ( P = 0.0407; odds ratio = 6.217; 95% confidence interval = 1.080–35.782). The overall 5-year survival rate was 30.4%. Conclusions: Liver resection using standard TVE with hypothermic portal perfusion and venovenous bypass is associated with a high mortality rate. The identification of preoperative predictors of mortality should improve the selection of patients for this aggressive surgery. Compared with nonsurgical management, the long-term results are acceptable and justify this aggressive surgery in selected patients. Abstract : Hepatectomy with standard total vascular exclusion of the liver, hypothermic portal perfusion, and venovenous bypass achieves a 5-year survival rate of 34% and has a 90-day mortality rate of 19.5%. Comorbidities and large tumors are independent predictors of 90-day mortality. A stringent selection of candidates is needed to further justify this aggressive surgery.